Nomogram and scoring system for preoperative prediction of the risk of systemic inflammatory response syndrome in one-stage flexible ureteroscopy lithotripsy - Zhou, Yuan; Zhang, Haiyan; Zhang, Rentao; Ding, Yinman; Wang, Zhengquan; Lin, Changming (Frontiers in Surgery, 2025)
BackgroundFlexible ureteroscopy lithotripsy (FURL) is a prevalent intervention for the management of upper urinary tract stones (UUTS). Assessing the onset of systemic inflammatory response syndrome (SIRS) in patients during and postoperatively is a critical determinant in the decision-making process regarding the necessity of preoperative ureteral stenting prior to FURL.Materials and methodsA total of 340 patients with UUTS who underwent one-stage FURL were analyzed retrospectively. Least absolute shrinkage and selection operator and multivariate logistic regression analysis were used to screen out independent risk factors, subsequently developing a nomogram. The predictive performance was internally assessed using the concordance index (C-index), receiver operating characteristic curve, and calibration curve. Additionally, we evaluated the risk of SIRS in the context of one-stage FURL, considering the impact of various available variables.ResultsAge, urinary white blood cells, urine bacterial culture, and systemic immune-inflammation index (SII) were integrated to establish a nomogram for prediction of the risk of SIRS in patients undergoing one-stage FURL. The SII exhibited the highest odds ratio (OR = 30.356) for SIRS. The nomogram demonstrated a favorable predictive performance with a C-index of 0.964 (95% CI = 0.932–0.996), an area under the curve of 0.935, and a calibration curve validating its accuracy. We further developed a scoring system and classified the risk of SIRS into four grades.ConclusionThe developed nomogram and risk scoring system demonstrate favorable predictive ability and clinical serviceability for the personalized estimation of SIRS risk in UUTS patients undergoing one-stage FURL. It is advisable to place a ureteral stent prior to FURL in individuals with an SII exceeding 1,300 and meeting one of the following criteria: age > 60 years, urinary white blood cell levels of 1+/2+/3+, or positive urine bacterial culture. The insights provided may assist clinicians in selecting safer therapeutic approaches for UUTS patients.